Analisis Metode Pencatatan Persediaan Barang Dagang Berdasarkan SAK ETAP Pada CV Bali Made Kecamatan Gianyar - Juliyanti, Ni Luh Putu; Putra, I Made Endra Lesmana (Hita Akuntansi dan Keuangan, 2025)
The objective of this study is to establish the approach for documenting the inventory of goods at CV. Bali Made. This investigation employs qualitative analysis techniques, gathering data through observations and interviews regarding CV. Bali Made. The analytical method employed is comparative descriptive analysis, where the researcher elucidates the findings obtained from observations at the research site and compares them with the theoretical merchandise inventory recording method defined by SAK ETAP, which has evolved in academic circles. Based on the research outcomes and discussions, it can be inferred that CV. Bali Made has adopted the perpetual method of recording merchandise inventory as stipulated by SAK ETAP. This entails recognizing inventory expenses when the sold inventory aligns with the period in which the associated revenue is acknowledged. Additionally, any damaged goods are accounted for as loss expenses, and disclosure requirements apply to inventory valuations.